Effects of moving cupping therapy for plaque psoriasis: study protocol for a randomized multicenter clinical trial - Meng Xing; Xiaoning Yan; Suqing Yang; Linge Li; Liping Gong; Hongxia Liu; Rong Xu; Jie Chen; Luo Ying; Yiding Zhao; Yuepeng An; Yang Liu; et al. (Trials, 2020)
Abstract Background It is difficult to achieve a balance among safety, efficacy, and cost for the clinical treatment of plaque psoriasis. The current treatment of psoriasis often involves comprehensive therapy such as topical plasters, internal medicine, and phototherapy, which are expensive, and some of the drugs have serious side effects. Moving cupping is a type of cupping that has been used clinically for thousands of years in China. It has the advantage of being inexpensive and easy to perform. Therefore, it is widely used in public hospitals in China for psoriasis treatment. However, a comprehensive evaluation of the current clinical evidence of its efficacy is lacking. In this study, we aimed to evaluate the efficacy and safety of moving cupping to treat plaque psoriasis. Methods A multicenter, two-arm parallel group, single-blind, randomized, controlled trial will be conducted at six hospitals in China between August 1, 2019 and December 31, 2021. A total of 122 adult patients (aged 18–65 years) who meet the inclusion criteria are being recruited. Participants will receive either basic treatment combined with moving cupping therapy or basic treatment combined with moving cupping placebo. The treatment cycle will be 4 weeks, and the efficacy of treatment will be assessed weekly by the Psoriasis Area and Severity Index during the treatment period and follow-up visits at weeks 6 and 8. The body surface area, physician’s global assessment, Dermatology Life Quality Index, patient-reported quality of life, visual analog scale, Traditional Chinese Medication syndrome scoring scale, combined medication, and adverse events will also be recorded and compared to the relative baseline values. Discussion The findings of this trial may lead to better decisions regarding the treatment of plaque psoriasis. If the trial outcomes are considered favorable, this ancient Chinese medical therapy may be worthy of widespread use because of its convenience and low cost. Trial registration This study was registered on May 15,2019 at ClinicalTrials.gov with the identifier number NCT03952676.